Bioactive compounds of pigmented rice extracts reveal by NMR-based metabolomics - Netrprachit, Papichaya; Nuangchamnong, Nitra; Ramli, Nurul Shazini; Maulidiani, Maulidiani; Mediani, Ahmed; Zolkeflee, Nur Khaleeda Zulaikha; Jiamyangyuen, Sudarat; Abas, Faridah (Taylor and Francis, 2023)
The present study determined total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, ±-glucosidase, and nitric oxide (NO) inhibitory activities of black (BR), purple (PR), and red rice (RR) extracted with different polarity solvents and characterized the metabolites by using the 1H NMR-based metabolomics approach. The methanol extract of RR had the highest DPPH scavenging and ±-glucosidase inhibitory activities. The water extracts of PR and RR exhibited the highest NO inhibitory activity with IC50 values of 176.28 ± 18.78 and 160.69 ± 14.83 µg/mL, respectively. The metabolites that contribute to radical scavenging and ±-glucosidase inhibitory activities of RR methanol extract were chlorogenic acid, protocatechuic acid, and tyrosine, whereas nicotinic acid, ³-aminobutyric acid, and citric acid were the metabolites that contributed to the NO inhibitory activity of RR water extract. The RR extracts are potential sources of bioactive compounds with antioxidant and NO inhibitory properties.